Bank carbon risk index - A simple indicator of climate-related transition risks of lending activity - László Bokor (Magyar Nemzeti Bank, 2021)
I propose a simple indicator of climate-related transition risks of banks' lending activity based on transaction-level loan data. The underlying idea is that the higher the greenhouse gas intensity of an economic activity (and so a debtor), the higher its transition risk. Recent Hungarian trends of this indicator alerts to significantly regrowing risks.
Keywords: C43; G21; Q54; 330; climate change; transition risk; greenhouse gas intensity; lending activity; risk indicator